Antibiogram of bacterial pathogens causing mastitis among cattle - YADAV, RAHUL; KUMAR, PANKAJ; PRAKASH, ANAND; BHANOT, VANDNA; CHEEMA, PAWANJIT SINGH; JINDAL, NARESH (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to detect mastitis in cattle milk samples and sensitive antibiotics for therapeutic uses. Milk samples from cattle (n = 1649) were tested for detection of mastitis by white side test (n = 1314) and culture examination (n = 335). Overall, 79.8% and 96.72% milk samples were positive by white side test and culture examination, respectively. Clinical mastitis and sub clinical mastitis were detected in 16.55% and 83.44% samples, respectively on the basis of presence of any clinical signs in milk or udder of animal. Gram-positive and gramnegative organisms were detected in 99.38% and 45.34% of the samples, respectively. Mixed infection of both was detected in 38.88% samples. More than 74% of both gram-positive and gram-negative isolates were found sensitiveagainst enrofloxacin and chloramphenicol followed by amikacin (69.44%), gentamicin (68.73%), moxifloxacin (67.87%) and levofloxacin (61.73%). Organisms were detected as multidrug resistant (MDR) organisms depending upon their MAR index value.